Determinants of Bank Deposits in Ghana: A Cointegration Approcah - Larbi-Siaw, Otu; Lawer, Peter Angmor (Asian Journal of Economics and Empirical Research, 2015)
The study investigates the influence of selected macroeconomic and financial level variables on bank deposits in Ghana. It specifically examines the dynamic effect of deposit interest rate, inflation, monetary policy rate, growth of money supply and stock prices (All Share Index) on the level of bank deposits. The dataset for the study consisted of quarterly data spanning the years of 2000 to 2013 gathered from the Bank of Ghana (BoG) monetary time series database and the World development Indicator (WDI) database. Employing a Co-integration analysis and Fully Modified Ordinary Least Square (FMOLS), both short and long run elasticity’s of the model are estimated. The preliminary test for unit root indicated that all the variables are integrated of order one (an I (1) process) and the co-integration revealed the presence of one co-integrating equation. Empirical findings form the study indicates a significantly negative short-term impact of both inflation and growth of money supply of bank deposits in Ghana. The long-run effects of the various independent variables on bank deposit are also discussed. Some of the variables conformed to priori expectations, albeit insignificant. Appropriate measures are also recommended based on the findings thereof.